INFORMATION SECURITY AS AN OBJECT OF REGULATION IN THE LAW OF UKRAINE - Iryna M. Sopilko (Journal of International Legal Communication, 2021)
The study gives definitions of information security and related terms, such as cybersecurity, national security, and others, indicates the goals, objects, subjects of the concepts under consideration. The author also considers the features of the foundation and development of the information society in Ukraine, the components of its state information policy for ensuring information security, and identifies the key operations of activity of state bodies in the information sphere. The approaches of scientists who studied certain aspects of national and information security were analyzed, based on their work valuable conclusions were drawn and the conceptual basis of the article was formed. Independently, the definition and characteristics of external and internal threats to the information security of the country are given, methods for solving the problems arising in this connection are introduced, ways of ensuring the information security of the state are indicated. Information security in this study is considered as the central element of the national security of Ukraine, as well as a problematic issue in the field of information protection and ensuring the high-quality functioning of the information space. The author made an in-depth analysis of the existing regulatory and legal instruments for ensuring information security, pointed out their shortcomings, and gave recommendations for their further advancement. Also, recommendations are given to improve the current situation with the regulation of information security in the country, the directions of the state information policy are suggested and ways to ensure the continuity of the functioning of the information security system of Ukraine are indicated.